2013
DOI: 10.1111/mve.12012
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activity and physicochemical properties of a crude methanol extract of the larvae of the blow fly Lucilia cuprina

Abstract: The emergence of multidrug-resistant bacterial strains has prompted the reintroduction of maggot therapy in the treatment of chronic, infected wounds. Many previous studies have demonstrated the potent antibacterial activity of larval excretions/secretions of the blowfly Lucilia sericata (Meigen) (Diptera:Calliphoridae) against bacteria. However, the antibacterial activity of its sibling species, Lucilia cuprina (Wiedemann) (Diptera:Calliphoridae) against a wide range of pathogenic bacteria has never been dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…The production of larval extract was performed according to the published protocols by Teh et al [ 19 ] with slight modifications. Approximately 200 unsterile, 2 to 3 days-old fly larvae were collected from cow livers, cow lungs or moistened mouse pellet and transferred into a clean, disinfected 50 ml washing tube.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of larval extract was performed according to the published protocols by Teh et al [ 19 ] with slight modifications. Approximately 200 unsterile, 2 to 3 days-old fly larvae were collected from cow livers, cow lungs or moistened mouse pellet and transferred into a clean, disinfected 50 ml washing tube.…”
Section: Methodsmentioning
confidence: 99%
“…The resazurin-based turbidometric (TB) assay was adopted to demonstrate the inhibition effects of larval extract of S. peregrina and M. domestica against S. aureus, MRSA , P. aeruginosa and E. coli. The larval extract of L. cuprina was included into the study as another positive control in addition to standard antibiotics since its inhibitory effects had been demonstrated previously by Teh et al [ 19 ] and therefore can validate and corroborate the feasibility of this assay. Broth microdilutions were performed precisely according to the Clinical and Laboratory Standards Institute (CLSI) protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in concordance with findings of Huberman et al (2007) and Barnes et al (2010) on L. sericata hemolymph extract and ES, respectively, where significant bactericidal activity against P. aeruginosa than against S. aureus were recorded. Also, Teh et al (2013) found that L. cuprina larval methanol extracts at 0.78 and 1.56 mg/ml concentrations were able to inhibit more than 50% of P. aeruginosa and E. coli, respectively, while 3.13 mg/ml was necessary to inhibit 50% bacterial growth of Klebsiella pneumonia.…”
Section: Discussionmentioning
confidence: 97%
“…The secretions from sibling species L . cuprina have also been reported to have anti-microbial activity, suggesting that this may be a common feature of fly larvae [ 16 ].…”
Section: Introductionmentioning
confidence: 99%